Influence of Block Structure on Dock Floor and Foundation Under Moonpool of Docks - CHE Yue, LI Yun, ZHOU Bing, JIN Guolong, ZHU Xiaodong, ZHOU Dongrong (Shanghai Jiaotong Daxue xuebao, 2023)
In order to study the influence of the whole dock block on dock floor and foundation, the force condition of dock floor and foundation is calculated and compared under working conditions of independent block. From different thicknesses, the structure of whole block is analyzed and optimized, and the force condition of dock floor and foundation is calculated under working conditions of the whole block. The influence of pile-soil co-reaction on pile foundation is analyzed. The results show that the force condition of dock floor and foundation cannot meet the requirements when using independent block. The whole block can make the load more uniform, improve the force condition, and make force and cracks meet the requirements. When pile-soil co-reaction is considered, the pile force will be reduced. When the longitudinal line load is greater than that designed for the original dock, priority should be given to the whole block. The results can provide reference for similar projects in the future.